The judicial protection of the cases related to children through the accelerated implementation of decisions according to Jordan sharia court law no. 31 for the year 1959 and its amendments until 2016 - Al-Hunaiti, Firas; Al-Shurafat, Jihad (Jordan Journal of Islamic Studies, 2023)
The purpose of this study was to demonstrate the importance of expediting cases in which the child is the focus and subject of these cases, and where the young person fears harm if the litigation is prolonged. It allows the custodian to apply for an accelerated implementation decision based on the provisions of Jordanian legal system No. 31 of 1959 AD and its amendments until 2016, which authorized this judicial procedure. In this study, the researcher discussed this topic in two parts. First, the legal and linguistic definition of the term " accelerated implementation decision" is outlined. In the second part, the researcher provided the reasons and basis for consideration in the Jordanian legal system No. 31 of 1959 and its amendments up to 2016. Accounts and introductions to the procedures used by the Jordanian courts to emphasize the urgency of these cases before issuing these decisions. One of the key findings of this paper is that Islamic Shari’a established the origin of accelerated implementation of decisions which shows how the lawmaker is aware of the origin of Shari’a Court law as there are some laws that were passed to ensure the child optimum interest.